PEREMPUAN DALAM PROFESI KEPOLISIAN - Edwin Rizal (Indonesian Journal of Dialectics, 2011)
Historically and traditionally police often be seen as a masculine profession, it is characterized by a very limited number of women who served as a police officer that prevent and control of crime and to maintain stability and order in society. The purpose of this study was to elaborate the pattern of communication and self-identity of policewoman as part of an effort to understand their role presence in the world who already perceived as a working area of the male. The perspective of this study is use the symbolic interaction that aimed at the six informant  who worked as a policewomen and served at Kepolisian Resor Kota Besar Bandung. The results of this study showed that communication patterns are occur in the form of ‘absorption instructions’, which means that all the informant is always taking orders on her assignment without any word or protest.  This study was also found that there are two policewomen identity, there were police women and women police who categorized through preposing gender aspects or assignment as a marker of identity that is more dominant. The policewomen sometimes receive treatment of gender inequality and accept it as far as it is beneficial presence as women, particularly in the characterization itself in domestic functions.